Quantitative Variation in Protein Content During Storage by Fungi in Some Pulses - Panchal V. H.3, Syed I. M.1, Lakde H. M.2* (Journal of Ecobiotechnology, 2011)
Pulses are rich sources of protein. Unfortunately the seeds of pulses are deteriorate by various fungi during storage. The present investigation was undertaken to study the quantitative variation in protein content during storage by fungi in pigean pea, green gram and chick pea. The study reveals that there was reduction in protein content as the storage period increases. Seven fungi were found to be dominant deteriorating the seeds of above mentioned three pulses.